Penerapan Pembelajaran Diferensiasi terhadap Motivasi Belajar Kelas V pada Permainan Bola Besar SDN 18 Mataram - Muhammad Iqbal Ghazali; Ahmad Zain Silahuddin; Azmi Ansor (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
This study aims to describe the learning style preferences of fifth-grade students at SDN 18 Mataram and to examine the implementation of differentiated instruction in the Physical Education, Sports, and Health (PJOK) subject. Using a qualitative descriptiveapproach, data were collected through questionnaires, observations, and interviews involving 26 students. The results show that most students preferred kinesthetic learning (45%), followed by visual (35%) and auditory (20%) styles. The teacher has begun to implement differentiated instruction by combining lectures, video presentations, and hands-on practice. However, the implementation is not yet fully optimal, particularly in terms of consistent use of visual media and structured verbal instruction. Conclusion: Differentiated instruction based on students’ learning style profiles is shown to be relevant for enhancing the effectiveness of PJOK learning. Applying such strategies supports more inclusive and adaptive classroom practices aligned with the principles of the Merdeka Curriculum. Teachers are encouraged to conduct continuous assessments of learning styles and to design instructional materials based on students’ individualneeds to improve both learning motivation and outcomes.